Effect of Mint and Rosemary Aromatic Oil Extracts on the Mortality of the Stored Date Pest Ephestia cautella (Walker) - Saraha Ismail; Aseel Kemal Abdul Hussein (Journal of Tropical Crop Science, 2026)
Ephestia cautella is one of the most common insect pests of stored dates, causing quantitative and qualitative losses. Therefore, this research aimed to evaluate the insecticidal effect of oil extracts from peppermint (Mentha piperita) and rosemary (Rosmarinus officinalis) against different larval instars of the date moth under laboratory conditions, to promote botanicals as a safe and environmentally friendly alternative for managing insect pests. This study was conducted in the Advanced Laboratory of Entomology at the Faculty of Education for Women, University of Kufa, during 2024-2025. The academic year showed the contact and digestive effects of both oil extracts at concentrations of 2.5%, 5%, 7.5%, and 10% on the mortality of second- and fourth instar larvae of E. cautella. The results showed high efficacy of the tested plant oil extracts in causing mortality across both larval instars. The contact effect of mint extract was slightly more effective against second-instar larvae than fourth-instar larvae across all treatments, with mortality reaching 100% in most treatments and concentrations, except at 2.5%, where it recorded 80% mortality for second-instar larvae. With rosemary extract, mortality percentages among fourth-instar larvae were higher under contact than under digestive treatment at all concentrations. Most contact treatments achieved 100% mortality, even at the 10% concentration. Digestive treatments resulted in an 80% mortality rate of second-instar larvae and a 50% mortality rate of fourth-instar larvae. These results demonstrate the potential of peppermint and rosemary oil extracts as effective botanical insecticides for controlling the date moth.